2017
DOI: 10.1177/0363546517697956
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Assessment of Hip Capsular Repair and Reconstruction Procedures Using a 6 Degrees of Freedom Robotic System

Abstract: Although complete restoration of joint stability may not be fully achieved at time zero, capsular repair and reconstruction may lead to improved patient outcomes by bringing hip rotational movements nearer to normal values in the immediate postoperative period, especially in cases in which extensive capsulotomy is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
86
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 31 publications
3
86
1
Order By: Relevance
“…This ligament primarily restricts excessive hip extension and external rotation; thus, previous conventional hip arthroscopy and open surgical dislocation involve releasing the iliofemoral ligament to gain greater access to the femoral head and neck. In general, it was suggested that there were marginal differences in stability between common capsulotomy approaches (i.e., interportal and T-capsulotomy) 10,15,18 , and capsular closure restored motion to more similar intact conditions 9,10,12,14,15,18 . In studies involving similar stepwise capsular management, Philippon et al and Baha et al measured the differences in range of motion after each surgical stage during capsular management 15,48 .…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
See 3 more Smart Citations
“…This ligament primarily restricts excessive hip extension and external rotation; thus, previous conventional hip arthroscopy and open surgical dislocation involve releasing the iliofemoral ligament to gain greater access to the femoral head and neck. In general, it was suggested that there were marginal differences in stability between common capsulotomy approaches (i.e., interportal and T-capsulotomy) 10,15,18 , and capsular closure restored motion to more similar intact conditions 9,10,12,14,15,18 . In studies involving similar stepwise capsular management, Philippon et al and Baha et al measured the differences in range of motion after each surgical stage during capsular management 15,48 .…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
“…In general, it was suggested that there were marginal differences in stability between common capsulotomy approaches (i.e., interportal and T-capsulotomy) 10,15,18 , and capsular closure restored motion to more similar intact conditions 9,10,12,14,15,18 . In studies involving similar stepwise capsular management, Philippon et al and Baha et al measured the differences in range of motion after each surgical stage during capsular management 15,48 . Although both studies demonstrated that common arthroscopic capsulotomy procedures (i.e., portal placement, interportal capsulotomy, and T-capsulotomy) increased the envelope of hip motion (internal-external rotation, abduction-adduction, and flexion-extension), their capsular repair and reconstruction helped to partially restore normative range of motion of the joint.…”
Section: Surgical Management Hip Preservation Capsulotomy and Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies explored the biomechanical contributions of local hip anatomy to stability, 4,5 and this evolved into a greater understanding of how the capsule itself taken together with pericapsular structures contributes to hip stability. 3,[6][7][8] More recently, the debate over the importance of capsular repair 9,10 and various repair strategies [11][12][13] has culminated with several outcome studies that leave no question as to the evidence in support of superior surgical outcomes with capsular repair. 14,15 Yes, folks, it is quite clear that the capsule must be addressed during routine arthroscopy.…”
Section: See Related Article On Page 116mentioning
confidence: 99%